DNA barcoding and morphological data reveal a new Hyposoter (Hymenoptera: Ichneumonidae: Porizontinae) reared from a rare zygaenid moth Artona flavipuncta Hampson, 1900 in Taiwan - Chen, Young-Fa; Huang, Chia-Lung; Hsu, Yu-Feng (Zootaxa, 2017)
A new species of Hyposoter Foerster, 1869 is discovered based on morphology of adults and cocoons, biology, and DNA barcoding evidence. It is herein described as Hyposoter distriangulum Chen, Huang & Hsu sp. nov. , which is a common parasitoid of a rare zygaenid moth Artona flavipuncta Hampson, 1900. The differences between similar Hyposoter species in Japan and Taiwan are also presented.